JENIS KESALAHAN PADA PEMBUKTIAN MATEMATIS: SYSTEMATIC LITERATURE REVIEW (SLR): The Types Of Errors In Mathematical Proof: Systematic Literature Review (SLR) - M. Fauzan Zannurrain; Rusi Ulfa Hasanah; Sulthon Zulkarnain Siregar (Yayasan Al-Amin Qalbu, 2024)
This research aims to conduct a literature review related to the types of errors in mathematical proofs. The research method used in this study is Systematic Literature Review (SLR). From the search results on Google Scholar, a total of 24 articles were found. These were then filtered according to specified criteria, which included only journal articles and excluded proceedings, theses, and dissertations. Articles from the period between 2017 and 2024 were considered, resulting in 22 articles after exclusion. Further screening was done based on the accreditation level of the journals (1-3) and reading the abstracts to assess their relevance to the research topic, which yielded 9 articles suitable for this study. The findings of this research indicate five main categories of errors: conceptual errors, logical errors, procedural errors, representation errors, and communication errors